2006
DOI: 10.1152/ajpregu.00709.2005
|View full text |Cite
|
Sign up to set email alerts
|

Studies of oxytocin and vasopressin gene expression in the rat hypothalamus using exon- and intron-specific probes

Abstract: To develop a comprehensive approach for the study of oxytocin (OT) and vasopressin (VP) gene expression in the rat hypothalamus, we first developed an intronic riboprobe to measure OT heteronuclear RNA (hnRNA) levels by in situ hybridization histochemistry (ISHH). Using this 84-bp riboprobe, directed against intron 2 of the OT gene, we demonstrate strong and specific signals in neurons confined to the supraoptic (SON) and paraventricular (PVN) nuclei of the rat hypothalamus. We used this new intronic OT probe,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 49 publications
(62 reference statements)
5
29
1
Order By: Relevance
“…Since both neuropeptides are robustly and equivalently secreted from the neurohypophysis following acute salt-loading (Stricker and Verbalis, 1986), it had always been assumed that the gene expression responses of the OXT and AVP magnocellular neuron (MCN) phenotypes to osmotic perturbations would also be equivalent. However, our previous studies (Yue et al, 2006) suggested that there is a significant difference in the excitation-transcription coupling mechanisms that regulate these two neuropeptide genes in the rat MCN. Given the above finding that the Oxt and Avp MCNs' gene expression responses after acute osmotic stimuli are so dramatically different, in contrast to their similar evoked secretory responses, we sought to determine whether direct application of the presumed neurotransmitter signals for secretion (Sladek, 2000(Sladek, , 2004Burbach et al, 2001) onto the SONs would also produce different transcriptional responses in the OXT and AVP MCN's.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Since both neuropeptides are robustly and equivalently secreted from the neurohypophysis following acute salt-loading (Stricker and Verbalis, 1986), it had always been assumed that the gene expression responses of the OXT and AVP magnocellular neuron (MCN) phenotypes to osmotic perturbations would also be equivalent. However, our previous studies (Yue et al, 2006) suggested that there is a significant difference in the excitation-transcription coupling mechanisms that regulate these two neuropeptide genes in the rat MCN. Given the above finding that the Oxt and Avp MCNs' gene expression responses after acute osmotic stimuli are so dramatically different, in contrast to their similar evoked secretory responses, we sought to determine whether direct application of the presumed neurotransmitter signals for secretion (Sladek, 2000(Sladek, , 2004Burbach et al, 2001) onto the SONs would also produce different transcriptional responses in the OXT and AVP MCN's.…”
Section: Introductionmentioning
confidence: 90%
“…There were also efforts made to develop intron-specific riboprobes for studying oxytocin (Oxt) gene expression (Brooks et al, 1993). However, use of this intron 1-based probe was found to produce variable results (Rivest and Laflamme, 1995;Yue et al, 2006). Therefore, we developed and validated a new Oxt intron-specific riboprobe, and used this new probe, together with other well-established intron-and exon-specific Oxt and Avp probes to reevaluate Oxt and Avp gene expression in the hypothalamus under various classical physiological conditions (Yue et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to VP, its systemic release from the posterior pituitary has long been known to be induced by osmotic and volumetric challenges (Bisset and Chowdrey, 1988;Verney, 1947), and governed by magnocellular neuronal firing activity (Poulain and Wakerley, 1982). Studies using ISHH using intronic probes have shown that transcription of the VP gene also occurs in magnocellular neuroendocrine cells under these conditions (Arima et al, 1999;Herman et al, 1991;Kakiya et al, 2000;Kawasaki et al, 2005;Onaka et al, 2003;Yue et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic osmotic stimulation in vivo and extended exposure of HNS explants to hypertonicity results in increased VP mRNA in SON [5,103,107]. This reflects increased VP gene transcription as indicated by increases in VP heteronuclear RNA [26,104]. Estrogen prevented the increase in VP mRNA in osmotically-stimulated HNS explants [88] suggesting an inhibitory role for ERβ in regulation of VP gene expression in VP magnocellular neurons.…”
Section: Effects On Neurohypophyseal Peptide Gene Expressionmentioning
confidence: 99%